An Assessment of the Dubai Metro Service's Performance Using SCOR Model and ARENA Simulation. Issue 3 (September 2020) - Kamarudeen, Niyazudeen; Sundarakani, Balan; Manikas, Ioannis
Metro service operations have become challenging in modern urban environments due to the dynamics of population, service levels, accuracy and other operational issues. This research applies the supply chain operations reference (SCOR) model combined with the ARENA model simulation to examine the service performance in the Dubai Metro. The proposed approach takes into consideration the real-time flows of metro service operations and simulates the passengers' service time in selected terminals. The researchers measure the actual time spent by passengers and estimate various possible scenarios as outcome. The researchers assessed the average time spent in the system and the performance improvement as a visualized outcome, with suggestions for improvements, such as: onboard card recharge, automatic checkout using radio-frequency identification (RFID) systems, integration of systems using the Internet of things (IOT) and blockchain and a dedicated lane system. The proposed recommendationshave the potential to contribute to service performance improvement of the metro rail, as Dubai plans for its operational expansion process towards Expo 2020. This research methodology and these results can be extended to metro service operations of other urban centres, to better understand passengers' behaviour in the future. In view of this, the research contributes to both the theory and practice of travel behaviour in the metro transportation service.